False genital tumors sphere - Esteves Flores, Augusto (2015)
2 cases of malignant tumors of the gastrointestinal tract, intestinal tract, and more epilón, who mistakenly received the diagnosis of ovarian cyst are presented. Two correspond to malignant tumors, in which it was necessary to remove part of the bowel segment. Rules are set to prevent the difficulties of differential diagnosis.